Linear and nonlinear fractional hereditary constitutive laws of asphalt mixtures - Di Mino, Gaetano; Airey, Gordon; Di Paola, Mario; Pinnola, Francesco Paolo; D’Angelo, Giacomo; Presti, Davide Lo (Taylor & Francis, 2016)
The aim of this paper is to propose a fractional viscoelastic and viscoplastic model of asphalt mixtures using experimental data of several tests such as creep and creep recovery performed at different temperatures and at different stress levels. From a best fitting procedure it is shown that both the creep one and recovery curve follow a power law model. It is shown that the suitable model for asphalt mixtures is a dashpot and a fractional element arranged in series. The proposed model is also available outside of the linear domain but in this case the parameters of the model depend on the stress level.